Stress-strain model for fibre-reinforced polymer confined rectangular columns - Koksal, Hasan Orhun; Doran, Bilge (ICE PUBL, 2011)
Applying fibre-reinforced polymer sheets around existing columns is an innovative technique in the field of civil engineering due to their high stiffness and strength-to-weight ratio, corrosion resistance and potentially high durability. The confinement effect of high-stiffness fibre jackets simply results in an increase in the compressive strength of columns. Various constitutive models have been constructed to predict the increase in the axial strength of concrete due to the confinement effect of fibre-reinforced polymer laminates. In this paper, a new stress-strain model is proposed for square/rectangular concrete columns confined with fibre-reinforced polymer jackets. The model is an extension of previous work on circular columns, adopting a previously proposed relation to plot the stress-strain curves. The proposed model utilises a failure criterion of concrete under triaxial compression, unlike the most existing models which rely on a previously presented general formulation. A large comparative study of 163 square/rectangular concrete specimens is performed on the basis of the prediction accuracy of existing models and the proposed approach for their ultimate strengths in compression. The recommended axial stress-strain plots are used to simulate the uniaxial compressive tests. The results confirmed that the axial stress-strain relationship evaluated by the presented technique can appropriately describe the deformation under uniaxial compressive loading.
Keywords: columns; composite structures; stress analysis; JACKETED CONCRETE COLUMNS; COMPRESSIVE BEHAVIOR; STRENGTH; MEMBERS; COMPOSITES; SHEETS; Construction & Building Technology; Engineering